Traumatic Obturator Hip Dislocation with Marginal Femoral Head Fracture in a 15-Year-Old Adolescent: A High-Energy Trauma—A Case Report and a Review of the Literature - Yoann Durand; Clémence Bruyère; Marco Saglini; Aurélien Michel-Traverso (Case Reports in Orthopedics)
We report the case of a 15-year-old boy brought to the emergency department after a bike accident, complaining of an isolated left hip pain. The X-rays showed an obturator hip dislocation treated by closed reduction under general anaesthesia, followed by 6 weeks of discharge. The follow-up MRI performed 6 weeks after the trauma showed an avascular femoral head necrosis, for which we performed multiple retrograde femoral head drilling, completed by the injection of autologue stem cells from the iliaq crest. One year later, the patient has no hip pain, no joint limitation, and can practice BMX at a high level again. The purpose of this report is to make the physicians aware of this rare problem that may be damaging for hip function, especially in young people.